Building high-tech product companies - Bowen, James E. (Thomson/South-Western, 2004)
A perfect blend of technology and entrepreneurship, Building High-Tech Product Companies equips entrepreneurs and managers with the tools necessary to grow a technologically driven company, as it delivers insightful information on how to anticipate the market and the technology and develop strategy, while perfecting management techniques. James Bowen uses the Maelstrom paradigm, which is the simultaneous pull of a Technology Life Cycle, a Product Life Cycle, and an Adoption of Innovation Life cycle on a company. This offers executives and managers better understanding of market and technology trends to help them form clear strategies for product development and release. It also includes interviews from dozens of executives from high-tech companies that have introduced successful products into the marketplace